Clinical Features and Natural History of Preadolescent Nonsyndromic Hypertrophic Cardiomyopathy - Norrish, Gabrielle; Cleary, Aoife; Field, Ella; Cervi, Elena; Boleti, Olga; Ziółkowska, Lidia; Olivotto, Iacopo; Khraiche, Diala; Limongelli, Giuseppe; Anastasakis, Aris; Weintraub, Robert; Biagini, Elena; et al. (Journal of the American College of Cardiology, 2022)
Up to one-half of childhood sarcomeric hypertrophic cardiomyopathy (HCM) presents before the age of 12 years, but this patient group has not been systematically characterized. The aim of this study was to describe the clinical presentation and natural history of patients presenting with nonsyndromic HCM before the age of 12 years. Data from the International Paediatric Hypertrophic Cardiomyopathy Consortium on 639 children diagnosed with HCM younger than 12 years were collected and compared with those from 568 children diagnosed between 12 and 16 years. At baseline, 339 patients (53.6%) had family histories of HCM, 132 (20.9%) had heart failure symptoms, and 250 (39.2%) were prescribed cardiac medications. The median maximal left ventricular wall thickness z-score was 8.7 (IQR: 5.3-14.4), and 145 patients (27.2%) had left ventricular outflow tract obstruction. Over a median follow-up period of 5.6 years (IQR: 2.3-10.0 years), 42 patients (6.6%) died, 21 (3.3%) underwent cardiac transplantation, and 69 (10.8%) had life-threatening arrhythmic events. Compared with those presenting after 12 years, a higher proportion of younger patients underwent myectomy (10.5% vs 7.2%; P = 0.045), but fewer received primary prevention implantable cardioverter-defibrillators (18.9% vs 30.1%; P = 0.041). The incidence of mortality or life-threatening arrhythmic events did not differ, but events occurred at a younger age. Early-onset childhood HCM is associated with a comparable symptom burden and cardiac phenotype as in patients presenting later in childhood. Long-term outcomes including mortality did not differ by age of presentation, but patients presenting at younger than 12 years experienced adverse events at younger ages. [Display omitted]